Effect of Nigella sativa Oil on early menopausal symptoms and serum levels of oxidative markers in menopausal women: A randomized, triple-blind clinical trial - Roghayeh Azami; Azizeh Farshbaf-Khalili; Mahdi Mahdipour; Farhood Ghazi Firozsalar; Mahnaz Shahnazi (Kashan University of Medical Sciences, 2022)
Background: The declining levels of estrogen during menopause are linked with numerous somatic and psychological complications. Objectives: This study aimed to examine the effect of Nigella sativa (N. sativa) oil on early menopausal symptoms and serum levels of some oxidative markers in postmenopausal women. Methods: This randomized placebo trial was conducted on 72 menopausal women aged 45-60 years. Participants were randomly allocated to placebo and intervention groups with an equal allocation ratio (1:1). Patients in the intervention group received one N. sativa oil capsule (1000 mg), whereas the placebo group received a placebo capsule at night for 8 weeks. Data were collected through the demographics questionnaire, the Greene's Climacteric Scale, and a form for recording the number of daily hot flashes. Furthermore, the serum levels of total antioxidant capacity (TAC) and malondialdehyde (MDA) were measured before and 8 weeks after the intervention. Data were analyzed using the independent-samples t, Chi-square, Mann-Whitney U, and Friedman tests as well as the repeated-measures analysis of variance. Results: The participants were matched in baseline values. The mean baseline score of the Greene's scale was 22.5 ± 9.5 in the intervention group and 20.0 ± 8.0 in the placebo group (P = 0.397). Mean scores had significantly reduced in both groups at the end of weeks 4 and 8. However, the intervention group experienced a more remarkable decrease in Greene's score (adjusted MDLog10 = −0.16 (−0.29 to −0.05); P = 0.019). There were no significant differences between the two groups in the subscales of Greene's scale (P > 0.05). No significant difference was observed between the groups in serum levels of TAC (P = 0.250) and MDA (P = 0.444). Conclusion: N. sativa reduced the total score of menopausal symptoms and hot flashes in menopausal women; however, it had no significant effect on the serum levels of oxidative stress markers.